Using complaints from obstetric care for improving women's birth experiences - a cross sectional study - Sisse Walløe; Søren Bie Bogh; Søren Fryd Birkeland; Lone Kjeld Pedersen; Annemette Wildfang Lykkebo; Lise Lotte Torvin Andersen; Britta Frederiksen-Møller; Lars Morsø (BMC, 2023)
Abstract Introduction Staff shortages and quality in obstetric care is a concern in most healthcare systems and a hot topic in the public debate that has centred on complaints about deficient care. However there has been a lack of empirical data to back the debate. The aim of this study was to analyse and describe complaints in obstetric care. Further, to compare the obstetric complaint pattern to complaints from women about other hospital services. Materials and methods We used the Healthcare Complaints Analysis Tool to code, analyse and extract contents of obstetric complaint cases in a region of Denmark between 2016 and 2021. We compared the obstetric complaint pattern to all other hospital complaint cases in the same period regarding female patients at a large University Hospital in a cross-sectional study. Results Complaints regarding obstetric care differed from women's complaints regarding other healthcare services. Women from obstetric care raised more problems per complaint, and tended to complain more about relational issues indicated by odds for complaints about staff shortage four times higher in the obstetric care group. Women from obstetric care had a lower proportion of compensation claims. Conclusion Systematic complaint analysis acknowledged women's experience in obstetric care and may point to areas that potentially need further attention. Complaints from obstetric care show that women experience deficiencies related to relational problems like recognition and individualized support compared to complaints from women receiving other hospital healthcare services.